Age-specific cyclical effects in job reallocation and labor mobility - Anne C. Gielen; Jan C. van Ours (Institute for the Study of Labor (IZA), 2005)
We present an empirical analysis of job reallocation and labor mobility using matched worker-firm data for the Netherlands to investigate how firms adjust their workforce over the cycle. Our data cover the period 1993-2002. We find that cyclical adjustments of the workforce occur mainly through fluctuations in job creation for young and prime-age workers while for old workers they occur mainly through fluctuations in job destruction. Moreover, we find that business cycle fluctuations are used to rejuvenate the workforce. Workforce reductions are most harmful for old workers; for them the flow out of employment is a one-way street.
Keywords: J23; J62; J63; 330; job creation; job destruction; accessions; separations; matched worker-firm data; Arbeitsmobilität; Beschäftigung; Arbeitsmarkt; Schätzung; Niederlande